2020
DOI: 10.5195/ijms.2020.486
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects Immunomodulators on Probiotics in COVID-19 Preventing Infection in the Future. A Narrative Review

Abstract: After the outbreak in December 2019, Coronavirus Disease (COVID-19) has become a global health problem because of its rapid spread throughout the world. To date, there are no effective therapies to treat or prevent COVID-19 infection. Probiotic bacteria are widely used to prevent gastrointestinal infections by modulating intestinal microbiota. Therefore, this literature review focuses on the potential possessed by probiotic bacteria for the prevention of future COVID-19 infections. Information was extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A limitation of the study was, however, the non-randomisation design of the probiotic element, but as mentioned in the methods section above, the number of participants who would have bought their own probiotics would have negated any comparative data. Nevertheless, this data does support studies which have demonstrated that probiotic supplements, particularly in vulnerable groups, shortened the incidence, duration and severity of respiratory and systemic symptoms associated with upper respiratory tract infections [6,13,15,40,54,[61][62][63][64][65][66][67][68][69][70][71][72][118][119][120]. It also supports two recent randomised trials involving patients and their relatives with COVID-19 [121,122].…”
Section: Discussionsupporting
confidence: 80%
“…A limitation of the study was, however, the non-randomisation design of the probiotic element, but as mentioned in the methods section above, the number of participants who would have bought their own probiotics would have negated any comparative data. Nevertheless, this data does support studies which have demonstrated that probiotic supplements, particularly in vulnerable groups, shortened the incidence, duration and severity of respiratory and systemic symptoms associated with upper respiratory tract infections [6,13,15,40,54,[61][62][63][64][65][66][67][68][69][70][71][72][118][119][120]. It also supports two recent randomised trials involving patients and their relatives with COVID-19 [121,122].…”
Section: Discussionsupporting
confidence: 80%
“… 1 Targeting the gut–lung microbiota axis by means of a high-fibre diet and probiotics may have anti-inflammatory effects in COVID-19 infection Review [ 157 ] 2 Microbiota Modulating Nutritional Approaches to Countering the Effects of Viral Respiratory Infections Including SARS-CoV-2 through Promoting Metabolic and Immune Fitness with Probiotics and Plant Bioactives Review [ 158 ] 3 Traditional Chinese medicine for COVID-19 treatment Review [ 159 ] 4 Gut microbiota and Covid-19- possible link and implications Review [ 160 ] 5 Probiotics and COVID-19 : one size does not fit all Review [ 161 ] 6 Potential Effects Immunomodulators on Probiotics in COVID-19 Preventing Infection in the Future. A Narrative Review Review [ 162 ] 7 The small intestine, an underestimated site of SARS-CoV-2 infection: from Red Queen effect to probiotics Review [ 60 ] 8 Considering the Effects of Microbiome and Diet on SARS-CoV-2 Infection: Nanotechnology Roles Review [ 163 ] 9 Antiviral effects of probiotic metabolites on COVID-19 Express Communication [ 164 ] 10 Using Probiotics to Flatten the Curve of Coronavirus Disease COVID-2019 Pandemic Review [ 165 ] 11...…”
Section: Recent Evidence Of Probiotics In Covid-19 - Preclinical and mentioning
confidence: 99%
“… 137 Moreover, probiotic administration lowered the viral loads directly via immune modulation against SARS-CoV-2 and reduced the secondary infection risk due to COVID-19. 138 The National Health Commission of China endorsed the use of probiotics for severe COVID-19 patients to restore intestinal balance as well as protect them from secondary infections. 139 Probiotics such as Bifidobacterium and Lactobacillus showed a decrease in the common cold, a symptom of SARS-CoV-2.…”
Section: Covid-19 Shows Lung Fungal Dysbiosismentioning
confidence: 99%
“…A systemic review compiled the antiviral efficacy of probiotics, and >20 strains have been shown to increase anti-inflammatory interleukins production and immune response . Moreover, probiotic administration lowered the viral loads directly via immune modulation against SARS-CoV-2 and reduced the secondary infection risk due to COVID-19 . The National Health Commission of China endorsed the use of probiotics for severe COVID-19 patients to restore intestinal balance as well as protect them from secondary infections .…”
Section: Covid-19 Shows Lung Fungal Dysbiosismentioning
confidence: 99%